Low peak‐to‐average power ratio and efficient multicarrier spread spectrum transceivers using hybrid and quadrature cyclic shift orthogonal keying. Issue 17 (27th October 2011) - Chiu, Yu‐Lun; Hwang, Jeng‐Kuang; Deng, Juinn‐Horng
ABSTRACT: This paper proposes two bandwidth and power efficient multicode multicarrier spread spectrum (MCSS) system modes based on a new cyclic shift orthogonal keying (CSOK) scheme that leads to low peak‐to‐average power ratio (PAPR) signals. Both system modes can improve the bandwidth efficiency by loading more data bits per symbol block. The first system mode is the hybrid CSOK (HCSOK) mode, which combines phase shift keying (PSK) or quadrature amplitude modulation (QAM) modulation symbol with the CSOK symbol, for example, the important hybrid quadrature PSK (QPSK)–CSOK case. The second is the quadrature CSOK (QCSOK) mode that transmits two parallel binary phase shift keying (BPSK)–CSOK branches at the same time. For both modes, maximum likelihood receivers are derived and simplified, leading to efficient fast Fourier transform‐based structures for maximum ratio combining and cyclic‐code correlation. Theoretical bit error rate (BER) analysis is conducted for the hybrid QPSK–CSOK case. Simulation results demonstrate that both the two system modes considerably outperforms the traditional Walsh‐coded MCSS system in terms of bandwidth efficiency, PAPR, BER, and antijamming capability. Furthermore, in indoor channel, QCSOK performs slightly worse than QPSK–CSOK, but it has almost twice the data rate when the code length is large. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : This paper proposes two bandwidths and power efficient multicode multicarrier spread spectrum (MCSS) system modes based on a new cyclic shift orthogonal keying scheme which leads to low‐peak‐to‐average power ratio (PAPR) signals. For both modes, maximum likelihood receivers are derived and simplified, leading to efficient fast Fourier transform‐based structures for maximum ratio combining and cyclic code correlation. Simulation results demonstrate that the two system modes considerably outperforms the traditional Walsh‐coded MCSS system in terms of bandwidth efficiency, PAPR, bit error rate and antijamming capability.